From precocious fame to mature obscurity: David Walker (1837–1917) MD, LRCSI, surgeon and naturalist to the Fox Arctic Expedition of 1857–59 - Froggatt, Peter; Walker, Brian M. (Journal of Medical Biography, 2012)
The Belfast-born David Walker was the 19-year-old surgeon and naturalist on the epic Fox Arctic Expedition (1857-59) that established the fate of Sir John Franklin's unsuccessful (1845) search for the North-West Passage. On return the crew were fê ted as heroes and decorated, and shared in a £5000 government bounty: Walker was also received by the Queen and (in Ireland) by the Lord Lieutenant, was honoured by the principal British and Irish natural history societies and his portrait was exhibited in the National Portrait Gallery, London. This paper describes his adventurous life, including the Fox Expedition, which from 1862 was spent abroad and included time in the Cariboo gold fields, service in the United States Army, practice in a notorious Californian frontier town and, in later life, the comparative quiet of general and occupational medical practice in Portland, Oregon. Once a household name, his death went unrecorded in the British and Irish medical and lay press.